The Relationship Between K-Workers’ Leader–Member Exchange, Organizational Citizenship Behavior and Task Performance—Evidence From Chinese Hospitals - Che, Xiaoli; Guo, Zhecheng; Chen, Qinyuan (Frontiers in Psychology, 2021)
Aim to solve the problem of difficult to manage and motivate knowledge workers’ (k-workers) in Chinese hospitals, this study examines the effect of k-workers’ Leader–Member Exchange (LMX) on task performance and the mediation effect of Organizational Citizenship Behavior (OCB) in China. Align the issue of the study and research objectives, this study gives some theoretical and managerial suggestions to company managers. In this study, 384 qualified questionnaires will be collected from k-workers in Chinese hospitals by using a self-administered survey, and the Partial Least Square Structural Equation Modelling (PLS-SEM) technique was employed for data analysis. This finding showed that LMX has positive relationship on OCB and task performance. The result also confirmed the mediation effect of OCB on the relationship between LMX and task performance. This research provided some implement to manage, motivate and inspire the k-workers and finally promote the organizational performance in Chinese hospitals.